The Significance of Serum S100A9 and TNC Levels as Biomarkers in Colorectal Cancer - Zhou, Minze (J Cancer, 2019)
Purpose: The aim of this study was to evaluate the diagnostic value of S100A9 and tenascin-c (TNC) levels as colorectal cancer (CRC) biomarkers in several ways, including through screening tests, differentiation tests, combination with existing biomarkers (CEA and CA19-9), and serum level measurements before and after surgery. Materials and Methods: In this case-control study, S100A9 and TNC serum levels were measured in 460 participants: 258 CRC patients, 99 patients with benign colonic disease (BCD) and 103 healthy donors (HD). Results: The serum levels of S100A9 were 22.32 (14.88-29.55) ng/ml, 10.02 (5.83-14.15) ng/ml and 10.05 (7.68-15.34) ng/ml in the CRC, BCD and HD groups, respectively. The serum levels of TNC were 4.30 (2.12-6.04) ng/ml, 1.60 (1.06-2.30) ng/ml and 2.00 (1.37-3.00) ng/ml in the CRC, BCD and HD groups, respectively. Significantly higher levels of both biomarkers (S100A9 and TNC) were found in CRC patients (both p<0.001). Both S100A9 and TNC levels were superior to CEA and CA19-9 levels as CRC diagnostic biomarkers; the combination of S100A9, TNC and CEA levels was an excellent biomarker with 79.8% sensitivity and 89.6% specificity. The serum levels of S100A9 and TNC in CRC patients were significantly lower after surgery than before surgery (p<0.01). Conclusion: S100A9 and TNC levels could serve as diagnostic biomarkers of colorectal cancer.